Exploration of the benefits of sunshine in hypertension sufferers: a literature review - Dwi Pitri, Angela; Wahyu Savitri, Elisabeth; Dwiana Widi Astuti, Agnes (Journal of Pubnursing Sciences, 2023)
Sunbathing consecutively every day for 15 days is a method to obtain benefits from sunlight. The purpose of this writing is to investigate the impact of sunlight on individuals with hypertension. This research involves a literature study of 15 articles published between 2022 and 2022, utilizing a combination of qualitative, quantitative, and correlation research methods. The findings indicate that 30-40% of hypertension cases take place during adulthood, with risk factors including habitual alcohol consumption leading to addiction, microvascular vasomotion failure triggered by excess sodium, arterial stiffness resulting from a lack of physical exercise, and calcium deficiency affecting peripheral vascular resistance. Sunbathing can result in a localised heating mechanism and an increase in lipid levels, which may lower blood pressure. From a nursing perspective, it is essential to consider the psychological aspects of hypertensive patients during treatment and encourage changes in their behaviour. This is a key aspect of cognitive-behavioural therapy. Conclusion: sunbathing may be a way of harnessing the benefits of sunlight to control blood pressure while encouraging behavioural change through a cognitive-behavioural therapy approach.